2017
DOI: 10.1590/1678-7757-2016-0500
|View full text |Cite
|
Sign up to set email alerts
|

Dentin pretreatment and adhesive temperature as affecting factors on bond strength of a universal adhesive system

Abstract: Objectives:To evaluate the effects of dentin pretreatment and temperature on the bond strength of a universal adhesive system to dentin.Material and Methods:Ninety-six extracted non-carious human third molars were randomly divided into 12 groups (n=8) according to Scotchbond Universal Adhesive (SbU) applied in self-etch (SE) and etch-and-rinse (ER) mode, adhesive temperature (20°C or 37°C) and sodium bicarbonate or aluminum oxide air abrasion. After composite build up, bonded sticks with cross-sectional area o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 25 publications
(61 reference statements)
0
35
0
5
Order By: Relevance
“…37,45,46 Also, there will be an increase in ionic reactions and functional monomer infiltration into dentin structure and collagen networks, thus resulting in more adhesive-tooth structure interactions and adhesion procedure. 35,36,47 Although laser radiation may increase bond strength and decrease marginal microleakage, the temperature changes were also measured in the present study due to the concerns about thermal necrosis of the pulp. It is reported that a 5.5°C increase in pulpal temperature causes a 15% chance of pulpal necrosis.…”
Section: Discussionmentioning
confidence: 96%
“…37,45,46 Also, there will be an increase in ionic reactions and functional monomer infiltration into dentin structure and collagen networks, thus resulting in more adhesive-tooth structure interactions and adhesion procedure. 35,36,47 Although laser radiation may increase bond strength and decrease marginal microleakage, the temperature changes were also measured in the present study due to the concerns about thermal necrosis of the pulp. It is reported that a 5.5°C increase in pulpal temperature causes a 15% chance of pulpal necrosis.…”
Section: Discussionmentioning
confidence: 96%
“…Fifteen only studied dentin's immediate micro-tensile strength 20,[51][52][53][54][55][56][57][58][59][60][61][62][63][64] , and 2 did not obtain detailed dentin micro-tensile strength values 65,66) . Finally, 15 in vitro studies were included and analyzed [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] .…”
Section: Search Strategymentioning
confidence: 99%
“…The qualitative synthesis of the studies included in this systematic review are summarized in Table 2 . Several strategies were identified: Air abrasion [ 58 , 59 ], application of crosslinking agents [ 57 , 60 , 61 , 62 , 63 , 64 , 65 ], application of dentin desensitizers [ 66 , 67 ], use of matrix metalloproteinases (MMP) inhibitors [ 10 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ], the use of the ethanol-wet bonding technique [ 78 ], application of an extra hydrophobic resin layer [ 56 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ], dentin pretreatment with laser [ 55 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ], multiple layer application [ 93 , 94 , 95 , 96 , 97 , 98 , 99 ], non-atmospheric plasma [ 100 , 101 ], prolonged curing time [ 102 ,…”
Section: Resultsmentioning
confidence: 99%